Impact of genetic heterogeneity in polymerase of hepatitis B virus on dynamics of viral load and hepatitis B progression. - Chi-Jung Huang; Chih-Feng Wu; Chia-Ying Lan; Feng-Yu Sung; Chih-Lin Lin; Chun-Jen Liu; Hsin-Fu Liu; Ming-Whei Yu (PLoS ONE, 2013)
OBJECTIVE: The hepatitis B virus (HBV)-polymerase region overlaps pre-S/S genes with high epitope density and plays an essential role in viral replication. We investigated whether genetic variation in the polymerase region determined long-term dynamics of viral load and the risk of hepatitis B progression in a population-based cohort study. METHODS: We sequenced the HBV-polymerase region using baseline plasma from treatment-naïve individuals with HBV-DNA levels≥1000 copies/mL in a longitudinal viral-load study of participants with chronic HBV infection followed-up for 17 years, and obtained sequences from 575 participants (80% with HBV genotype Ba and 17% with Ce). RESULTS: Patterns of viral sequence diversity across phases (i.e., immune-tolerant, immune-clearance, non/low replicative, and hepatitis B e antigen (HBeAg)-negative hepatitis phases) of HBV-infection, which were associated with viral and clinical features at baseline and during follow-up, were similar between HBV genotypes, despite greater diversity for genotype Ce vs. Ba. Irrespective of genotypes, however, HBeAg-negative participants had 1.5-to-2-fold higher levels of sequence diversity than HBeAg-positive participants (P<0.0001). Furthermore, levels of viral genetic divergence from the population consensus sequence, estimated by numbers of nucleotide substitutions, were inversely associated with long-term viral load even in HBeAg-negative participants. A mixed model developed through analysis of the entire HBV-polymerase region identified 153 viral load-associated single nucleotide polymorphisms in overall and 136 in HBeAg-negative participants, with distinct profiles between HBV genotypes. These polymorphisms were most evident at sites within or flanking T-cell epitopes. Seven polymorphisms revealed associations with both enhanced viral load and a more than 4-fold increased risk of hepatocellular carcinoma and/or liver cirrhosis. CONCLUSIONS: The data highlight a role of viral genetic divergence in the natural course of HBV-infection. Interindividual differences in the long-term dynamics of viral load is not only associated with accumulation of mutations in HBV-polymerase region, but differences in specific viral polymorphisms which differ between genotypes.